Study protocol for a pilot study for Remote ADHD Monitoring Program (RAMP) for children in rural areas - Claire A. MacGeorge; Matthew Henry; Hannah A. Ford; Lacy Malloch; Emily Fratesi; Shannon Cabaniss; Jaime Baldner; Melody Greer; Kristin Gaffney; Milan Bimali; Preetha Abraham; Linda Y. Fu; et al. (PLoS ONE, 2025)
Background Attention-deficit/hyperactivity Disorder (ADHD) is the most common neurobehavioral condition of childhood and can be controlled with stimulant medication. Evidence-based guidelines endorse use of standardized ADHD symptom reports to facilitate medication titration to therapeutic dosage. Children living in under-resourced areas experience barriers to receiving this recommended evidence-based care. The Remote ADHD Monitoring Program (RAMP) uses a text-based platform to relay symptom reports from caregivers and teachers to healthcare providers. This pilot study is a feasibility study examining intervention uptake. It compares the submission of structured symptom reports in those children enrolled in RAMP compared to usual care as well as utilization of the RAMP platform by providers. Methods This paper describes the protocol to evaluate the feasibility of deploying RAMP in practices serving rural or underserved children. We will recruit 36 dyads from 4 practices in 2 separate states. Each dyad will include a caregiver and their child aged 5–11 years with a diagnosis of ADHD who is starting or reinitiating stimulants. Dyads will be randomized 1:1 to receive the RAMP intervention or usual care with attention controls. Our primary outcome is number of symptom reports (paper assessments in control arm and RAMP reports in intervention arm) per participant that are completed by caregivers and teachers and returned to providers. Our secondary outcome is proportion of submitted RAMP reports that are reviewed by providers. Discussion As telehealth use increases, it is critical that we improve access to high quality care for children with chronic conditions. Leveraging technology may be a meaningful approach to improve efficiency in optimizing medication management. This pilot study tests a text-based platform designed to improve communication between the caregivers and teachers of children with ADHD and health care providers. If successful, a future trial will examine the effectiveness of the RAMP intervention on improvement in symptoms. Trial registration ClinicalTrials.gov NCT06743425 .